2018
DOI: 10.1016/j.addbeh.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of population smoking cessation by electronic cigarette use status in a national sample of recent smokers

Abstract: Among those with a recent history of smoking, daily e-cigarette use was the strongest correlate of being quit at the time of the survey, suggesting that some smokers may have quit with frequent e-cigarette use or are using the products regularly to prevent smoking relapse. However, the low prevalence of cessation among infrequent e-cigarette users highlights the need to better understand this subgroup, including the individual factors and/or product characteristics that may inhibit cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
96
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 29 publications
14
96
2
4
Order By: Relevance
“…The inverse correlation between vaping and smoking is consistent with other findings: Frequent EC use is associated with lower self‐reported cigarette smoking (Biener & Hargraves, ; Brose, Hitchman, Brown, West, & McNeill, ; Giovenco & Delnevo, ; Hitchman, Brose, Brown, Robson, & McNeill, ; Levy, Yuan, Luo, & Abrams, ; Subialka Nowariak, Lien, Boyle, Amato, & Beebe, ). Given the inverse correlation between EC use and CO levels, future research should determine if directly reinforcing EC use produces reductions in CO.…”
Section: Discussionsupporting
confidence: 89%
“…The inverse correlation between vaping and smoking is consistent with other findings: Frequent EC use is associated with lower self‐reported cigarette smoking (Biener & Hargraves, ; Brose, Hitchman, Brown, West, & McNeill, ; Giovenco & Delnevo, ; Hitchman, Brose, Brown, Robson, & McNeill, ; Levy, Yuan, Luo, & Abrams, ; Subialka Nowariak, Lien, Boyle, Amato, & Beebe, ). Given the inverse correlation between EC use and CO levels, future research should determine if directly reinforcing EC use produces reductions in CO.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our participants' perceptions, a recent report from the National Academies of Sciences, Engineering, and Medicine concluded that ECIGS are far less harmful than cigarettes . A recent meta‐analysis found that ECIGS may indeed increase smoking cessation and is consistent with national survey findings, yet the National Academies report concluded that there was “insufficient evidence” from randomized controlled trials that e‐cigarettes can help people quit smoking. Of note, approximately half of our sample successfully quit smoking using ECIGS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors noted that for the first time since 2001, overall quit rates had increased, suggesting that vaping has led to an increase in quitting at the population level 11. Analysing US data from the 2014 and 2015 National Health Interview Surveys, Giovenco and Delnevo found that among adults who had smoked in the past 5 years, daily vaping was the factor most strongly associated with smoking cessation 12. Longitudinal data reported by Zhang et al found that long-term vaping (at least 2 years) was associated with a fourfold higher odds of quitting than among non-users, adjusted for baseline characteristics of the sample 13.…”
mentioning
confidence: 99%